Renewable energy sources as an attractive element of industrial tourism. Issue 18 (12th December 2018) - Beer, Martin; Rybár, Radim; Kaľavský, Michal
Abstract : This paper deals with the overview of the interaction of tourism and renewable energy sources, and evaluates their potential regarding tourism industry as well as in terms of increasing of tourism attractiveness in the selected area. Renewable energy sources can be considered an attractive element within the industrial tourism and, in some cases, can increase the number of visitors to the area, mainly due to its modern design, proportions, eco-image and, in certain regions, due to its uniqueness. In analysis, interactions of renewable energy and tourism were classified into four categories. The analysis showed that the touristic subjects connected to the sensitively selected and located type of renewable energy source could have significant numbers of visitors in tens of thousands. According to results of the analysis, the highest number of visitors reached the visitor centres next to geothermal power plants and wind parks, which can be explained by their unique visual aspects. The paper also analysed the possible impact of the renewable energy infrastructure on tourists, when available studies indicate the minimal impact of installation if the power plants are sensibly placed in the country regarding location or distance from considered subject.